2020
DOI: 10.1111/jcpe.13385
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal surgery using rhFGF‐2 with deproteinized bovine bone mineral or rhFGF‐2 alone: 2‐year follow‐up of a randomized controlled trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…It is of interest to note that, in comparison between the FGF-2 + DBBM and FGF-2 alone groups, no significant difference was found in the micro-CT and histological results. This finding was in line with our clinical observations [12,21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is of interest to note that, in comparison between the FGF-2 + DBBM and FGF-2 alone groups, no significant difference was found in the micro-CT and histological results. This finding was in line with our clinical observations [12,21].…”
Section: Discussionsupporting
confidence: 93%
“…Combined use of signaling molecules and bone substitutes is clinically recommended for the treatment of deep noncontained intrabony defects [56,57]. In our recent clinical study [21], the treatment of intrabony defects with FGF-2 + DBBM yielded significantly greater RBF when compared with FGF-2 alone at 2 years postoperatively, in cases of 1-2-wall defects. This presented the possibility that such combination therapy may be clinically beneficial in certain bone defect configurations.…”
Section: Discussionmentioning
confidence: 86%
“…These findings were similar to those of previous animal studies evaluating periodontal wound healing/regeneration following rhFGF‐2/DBBM application (Sakata et al, 2006; Murakami et al, 2021). Additionally, a recent report indicated that the treatment of intra‐bony defects with rhFGF‐2/DBBM yielded significantly greater radiographic bone fill compared with rhFGF‐2 alone, particularly in one‐ and two‐wall defects (Aoki et al, 2021). These positive results may be explained by in vitro data demonstrating that rhFGF‐2 promotes cell viability, proliferation, angiogenesis, and osteogenic differentiation on DBBM (Murakami et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor‐2 (FGF‐2), a member of the heparin‐binding growth factor family, is involved in broad mitogenic and cell survival activities, including angiogenesis, wound healing, and embryonic development. Topical application of recombinant human FGF‐2 (rhFGF‐2) was found to support periodontal regeneration without ankylosis or epithelial down‐growth in periodontal intra‐bony defects in several animal studies (Anzai et al, 2010; Shirakata et al, 2010, 2013; Murakami et al, 2021) and promoted CAL gain and alveolar bone gain in humans (Kitamura et al, 2011, 2016; Aoki et al, 2021). Moreover, new bone formation was found to be more extensive in rhFGF‐2‐treated sites compared with enamel matrix derivative‐treated sites in human/animal intra‐bony defects (Shirakata et al, 2010; Ninomiya et al, 2013; Kitamura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation